The Effect of Physical Boundaries Education on Knowledge of Child Sexual Abuse Prevention among Preschool-Aged Children at As-Sakinah Kindergarten, Medan Amplas, in 2025 - Zuidah Zuidah; Srimis Leini Saragih (Benih : Journal of Midwifery, 2025)
Preschool-aged children are vulnerable to Child Sexual Abuse (CSA) because they have not yet fully understood body boundaries and have difficulty recognizing dangerous situations. CSA cases have increased by 49.31% since 2020 and can cause severe trauma, potentially leading victims to become perpetrators in the future. This study aims to determine the effect of Physical Boundaries Education on knowledge of CSA prevention among preschool-aged children. This study employed a pre-experimental method with a one-group pretest–posttest design. The sampling technique used was total sampling, resulting in a total sample of 30 respondents. Data were collected using questionnaires, and data analysis was conducted using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. The results showed a difference in children’s knowledge before and after receiving Physical Boundaries Education. Prior to the intervention, the majority of children had poor knowledge (50%), whereas after the intervention, children’s knowledge increased to a good category (90%). The Wilcoxon test results indicated a p-value of 0.00 (< 0.05), demonstrating a significant effect following the intervention. In conclusion, Physical Boundaries Education has a significant effect on knowledge of Child Sexual Abuse prevention among preschool-aged children at As-Sakinah Kindergarten, Medan Amplas. It is expected that the school will continue this program through collaboration with the local Department of Education and involve parents in supervising and limiting children’s gadget use..